Os animais da terra : do texto literário aos formatos cinematográficos de roteiro e storyboard - Moraes, Michelle Marques de (2014)
In filmography that addresses the Amazon there are often impregnated productions with a colonizing and full vision of stereotypical characters, as in much of the literature produced in and on Amazon. Most have these Amazonian clichés, with rare exceptions, like the works of Milton Hatoum and Vicente Franz Cecim. The book "Earth's Animals", which makes up the "Journey to Andara" cycle - oO invisible book, Vicente Franz Cecim, is a case following an opposite direction, speaks of the Amazon, without being obvious, of transfigured form and metaphorical. Starting from this text, we sought, the possibility of transposing the literary work for the film formats script and storyboard, glimpse concretely a plastic proposal that works near the Amazon visuality suggested in the text. And in the work implementation process, when using the film language, observe the characteristics or fundamental structures of the text, to go through the adaptation, allow to remain with the identity of the work. As well as take advantage of this route of the creative process to understand, identify milestones, evaluate and reflect on possible ways to perform the semiotic transposition of that work, proposing the end, an aesthetic construction that matches the literary text, and contribute with the possibility of building an Amazonian filmography not stereotypical. KEYWORDS: Film; adaptation; storyboard; Amazon, Cecim